The spanish rural areas: territories where tourism is produced and consumed or sustainable tourism destination in a competitive environment? The case of northeast of Segovia - Fernando Martín Gil e Iris Martín Hernan (Boletín de la Asociación de Geógrafos Españoles)
Resumen